Kinematic analysis of cross on training and competition rings: comparison between elite and international level gymnasts - Carrara, P. D. S.; Irwin, G.; Exell, T.; Serrão, J. C.; Amadio, A. C.; Mochizuki, L. (Science of Gymnastics Journal, 2024)
Auxiliary devices are used to train gymnastics skills. Based on the principles of training specificity, this study aimed to investigate the effectiveness of a training device for the static cross posture on Men`s Artistic Gymnastics rings through kinematic analysis. Twelve national team gymnasts were divided into two groups, based on their competitive results: the elite group (age: 21.8±3.2 years) and the international group (age: 19.3±3.3 years) performed the cross three times under both conditions: standard competition rings, and training rings with an auxiliary device. The videos were digitised and analysed with shoulder angles as trunk and arm segments. The variables included the right and the left shoulder angles in the frontal plane, as well as any asymmetry of those angles. Two-way ANOVA (conditions versus groups) and individual t-test statistics were conducted. Both groups performed the cross on training rings with increased abduction at both right (p<0.001) and left (p<0.001) shoulders and reduced asymmetry (p=0.01) than on competition rings. These kinematic improvements would translate into competition-typical score improvements of 0.1 to 0.3 points, and enhanced shoulder joint stability. Hence, the training rings with an auxiliary device effectively replicate skill-specific joint angles, adhering to the kinematics principles of training specificity for the static cross posture on rings, thus benefiting both elite and international-level gymnasts.